GAMES OF EMPIRE TEN YEARS ON - Pelletier, Caroline; Ruffino, Paolo; Woodcock, Jamie; Bulut, Ergin; Nieborg, David; Fordyce, Robbie (AoIR Selected Papers of Internet Research, 2020)
The panel will retrospectively evaluate the significance of the seminal text Games of Empire (2009) for new media and game studies, reflecting on the contribution of autonomous Marxism to the study of digital culture today, as well as the methodological move it performed in tracing continuities and discontinuities between sites of production and play. Each paper will take one or two key concepts from the original book, including Empire, multitude, ideology, and cognitive capitalism, and apply them to the contemporary moment in the games sector. Our aim is to explore the strengths and limitations of these concepts, as well as identify the salient ways in which the sector has evolved over the last ten years. For example, we will examine efforts at unionisation in the sector; how gender and race have emerged as key concerns in the last few years in sites of game work; how apps are affecting the representation of capitalist and military systems; and how ‘multitude’ in the sector has assumed new forms in the wake of new distribution platforms. The panel will make a case for integrating social theory with the analysis of production cultures and textual practices, as well as situating the analysis of games within the field of new media and internet studies more broadly.